Phytochemicals from Kaempferia angustifolia Rosc. and their cytotoxic and antimicrobial activities - Tang, Sook Wah; Sukari, Mohd Aspollah; Neoh, Bee Keat; Yeap, Yunie Soon Yu; Abdul, Ahmad Bustamam; Kifli, Nurolaini; Ee, Gwendoline Cheng Lian (Hindawi Publishing Corporation, 2014)
Phytochemical investigation on rhizomes of Kaempferia angustifolia has afforded a new abietene diterpene, kaempfolienol (1) along with crotepoxide (2), boesenboxide (3), 2′-hydroxy-4,4′,6′-trimethoxychalcone (4), zeylenol (5), 6-methylzeylenol (6), (24S)-24-methyl-5 -lanosta-9(11), 25-dien-3 -ol (7), sucrose, -sitosterol, and its glycoside (8). The structures of the compounds were elucidated on the basis of spectroscopic methods (IR, MS, and NMR). Isolation of 6-methylzeylenol (6), (24S)-24-methyl-5 -lanosta-9(11), 25-dien-3 -ol (7), and -sitosterol-3-O- -D-glucopyranoside (8) from this plant species has never been reported previously. The spectroscopic data of (7) is firstly described in this paper. Cytotoxic screening indicated that most of the pure compounds tested showed significant activity with (4) showing the most potent activity against HL-60 (human promyelocytic leukemia) and MCF-7 (human breast cancer) cell lines. However, all extracts and most of the pure compounds tested were found to be inactive against HT-29 (human colon cancer) and HeLa (human cervical cancer) cell lines. Similarly, none of the extracts or compounds showed activity in the antimicrobial testing.